Is a Dry Eye Disorder in Firefighters an Occupational Disease? - Ay, İbrahim Ethem; Şenol, Yiğit; Gobeka, Hamidu Hamisi; Doğan, Mustafa (La Medicina del Lavoro, 2023)
Background: To examine firefighters (FFs) exposed to high levels of fire smoke and, as a result, to uncover risk factors for dry eye disorder (DED) compared to age-and gender-matched healthy individuals.Methods: In this cross-sectional study, 51 FFs from the Afyonkarahisar Municipality Fire Department were chosen at random (group 1). A control group (group 2) included 51 age- and gender-matched healthy individuals. The Ocular Surface Disease Index (OSDI) questionnaire was administered after all participants were thoroughly explained the study's objectives and procedures. Then, using a portable hand biomicroscope, an ocular exam was performed on-site. DED was defined as a non-anesthetic Schirmer test result of